The Role of Physiotherapy in Sports Injuries: Enhancing Prevention, Rehabilitation, and Athletic Performance – A Comprehensive Review - Asiri, Mohammed Yousef Tale; Alojaym, Abdulkarim Mohammed; Alqahtani, Saad Mohammed Abdullah; Alhadi, Abdulelah Ali Y; Alasiri, Saud Abdullah; Aljasser, Faisal Hamad Saleh; Alshamrani, Abdulaziz Ahmed Mohamed; Alqahtani, Naif Abdullah Mohammad; Alammari, Khalid Muidh Salem; Asiri, Mohammed Ali Hasan (Journal of Posthumanism, 2024)
Sports injuries remain one of the most significant challenges affecting athletes’ health, performance, and career longevity. Physiotherapy plays a critical role not only in the treatment and rehabilitation of these injuries but also in their prevention and the enhancement of athletic performance. This comprehensive review explores the multifaceted contributions of physiotherapy in sports medicine, focusing on three primary domains: injury prevention, rehabilitation, and performance optimization. Preventive physiotherapy strategies such as biomechanical screening, conditioning programs, and flexibility training reduce the risk of common injuries including anterior cruciate ligament (ACL) tears, ankle sprains, and muscle strains. Rehabilitation involves phased approaches encompassing pain management, mobility restoration, strengthening, and functional retraining, enabling safe and efficient return-to-sport decisions. Beyond recovery, physiotherapists also contribute to performance enhancement by addressing movement inefficiencies, improving load management, and implementing evidence-based recovery techniques. Despite these advancements, challenges such as limited access to specialized physiotherapy, cost barriers, and lack of standardized guidelines remain. Emerging innovations in tele-rehabilitation, wearable technology, and artificial intelligence offer promising directions for the future. Overall, physiotherapy remains indispensable in modern sports medicine, serving as a cornerstone for athlete health, injury resilience, and optimal performance outcomes.